Assessing Flood Vulnerability from Rapid Urban Growth: A Case of Central Java — Indonesia - DEWI, Retno Sari; HANDAYANI, Wiwandari; PRATAMA, Isnu Putra; De VRIES, Walter T.; RUDIARTO, Iwan; ARTININGSIH, Artiningsih (Chinese journal of urban and environmental studies (Print), 2023)
Urban growth, in many Asian cities, may lead to increased exposure to flood and growing sensitivity mainly because of the presence of informal settlements. On the other hand, urban areas may offer better access to public facilities, improving adaptive capacity and enhancing the local government’s capabilities. This study aims to investigate to what extent urban growth exacerbates flood vulnerability in Central Java. Concurrently, floods are the most frequent disaster in the area. The approach used in the vulnerability assessment involves socioeconomic conditions (population density, the number of impoverished families, public facilities) associated with three main aspects (exposure, sensitivity, and adaptive capacity), resulting in the Exposure and Sensitivity Index and the Adaptive Capacity Index. Scoring and weighting analysis using secondary data in a sub-district unit from the Central Bureau of Statistics are applied. The result shows that urban growth contributes to the escalation of hazards and vulnerability. On the other hand, a high population also increases the number of public facilities and affects adaptive capacity in certain areas. Indeed, strategic urban development policies are critical to manage the three elements that form the flood vulnerability.